The Moderating Role of Safety Leadership in the Relationship Between Safety Climate, Safety Behavior, and Safety Performance: Evidence from the Palm Oil Processing Industry in Indragiri Hulu, Riau, Indonesia - Rival Lino; Budiyanto B; Agustedi A (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study examines the moderating role of safety leadership behavior in the relationship between safety climate, safety behavior, and safety performance in the palm oil processing industry in Indragiri Hulu Regency, Riau, Indonesia. A quantitative approach was employed using data collected from 329 unit leaders across various operational divisions. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS to assess both direct and moderating effects. The findings reveal that safety climate has a positive and significant impact on safety performance, indicating that organizational commitment to safety and risk awareness are critical determinants of effective safety outcomes. In contrast, safety behavior does not show a significant direct effect on safety performance, suggesting that individual compliance and participation alone are insufficient without strong organizational support. Furthermore, safety leadership behavior is found to strengthen the relationship between safety climate and safety performance, highlighting the important role of leadership in reinforcing safety-related perceptions and practices. However, safety leadership behavior does not moderate the relationship between safety behavior and safety performance. These results contribute to the development of followership theory by emphasizing the interaction between leadership and employee roles in achieving organizational safety goals. The study underscores the importance of integrating strong safety leadership with a supportive safety climate to enhance safety performance in high-risk industrial settings.